Adversity Response Profile IT-assisted for Lectures Online during New Normal - Ardiansyah, Adi Satrio; Sari, Salsabilla Naura; Caesario, Nico (Universitas Negeri Semarang, 2021)
The Distance Education implemented by the government during New Normal has an impact on student learning activities and student lectures. To find out the ability of students to face problems in current conditions, it can be seen from the Adversity Quotient (AQ) which can be measured by the Adversity Response Profile (ARP). The purpose of this study was to develop valid and reliable IT-assisted ARP in online lectures during New Normal. The research method used was Research and Development (R&D) which was conducted on 50 students of the UNNES Mathematics Department. This development research consists of three stages, namely the initial investigation, the prototype phase and the assessment phase which will then be analyzed using quantitative analysis techniques. The results showed that the IT-assisted ARP met the valid and reliable criteria. The results show that the reliability value is very high, namely 0.98. With the discovery of valid and reliable ARP, educators can use it to determine the level of student ability in dealing with learning problems during the New Normal.